Rancang Bangun Sistem Informasi Manajemen Akademik Berbasis Web dengan Fitur Absensi Digital dan Computer Based Testing (CBT) pada SMP Pelita Bangsa Pamulang - sumarni marwati; LUQMANUL HAKIM MUBARAKH; Jupron (Universitas Lampung, 2026)
SMP Pelita Bangsa Pamulang still relies on conventional methods for managing academic data, including manual paper-based attendance and paper-based exam systems. This research aims to design and build a web-based Academic Management Information System (EduPortal) integrating digital attendance and Computer Based Testing (CBT) features. The system was developed using Single Page Application (SPA) architecture with Vanilla JavaScript on the frontend and PHP Native with MySQL. Blackbox Testing on 12 test scenarios all passed with 100% success rate. System Usability Scale (SUS) testing with 30 respondents yielded a cumulative average score of 82.5, categorized as